1
$\begingroup$

Using only rules of natural deduction, I am trying to prove that $$p \implies q \vdash \lnot p \lor q$$ but am having a lot of difficulty. I was able to prove the other direction.

Could anyone show me or point me to the right direction?

$\endgroup$
0
2
$\begingroup$

I assume that you are trying to prove : $p \to q \vdash \lnot p \lor q$.

1) $p \to q$ --- premise

2) $\lnot (\lnot p \lor q)$ --- assumed [a]

3) $\lnot p$ --- assumed [b]

4) $\lnot p \lor q$ --- from 3) by $\lor$-intro

5) $\bot$ --- from 2) and 4)

6) $p$ --- from 3) and 5) by $\lnot$-elim, discharging [b]

7) $q$ --- from 1) and6) by $\to$-elim

8) $\lnot p \lor q$ --- from 7) by $\lor$-intro

9) $\bot$ --- from 2) and 8)

10) $\lnot p \lor q$ --- from 2) and 9) by $\lnot$-elim, discharging [a].

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.